Opposite effects of short-term and long-term St John's wort intake on voriconazole pharmacokinetics - Rengelshausen, Jens; Banfield, Maria; Riedel, Klaus-Dieter; Burhenne, Jürgen; Weiß, Johanna; Thomsen, Torben; Walter-Sack, Ingeborg; Haefeli, Walter E.; Mikus, Gerd (Clinical pharmacology & therapeutics, 2005)
Objectives Constituents of St John's wort (SJW) in vivo induce the cytochrome P450 (CYP) isozymes 3A4, 2C9, and 2C19 but in vitro were shown to inhibit them. This study investigates both short- and long-term effects of SJW on the antifungal voriconazole, which is metabolized by these enzymes. Methods In a controlled, open-label study, single oral doses of 400 mg voriconazole were administered to 16 healthy men stratified for CYP2C19 genotype before and on day 1 and day 15 of concomitant SJW intake (300 mg LI 160 3 times daily). Plasma and urine concentrations of voriconazole were determined by liquid chromatography with mass-spectrometric detection. Results During the initial 10 hours of the first day of SJW administration, the area under the voriconazole plasma concentration-time curve was increased by 22% compared with control (15.5 ± 6.84 h · μg/mL versus 12.7 ± 4.16 h · μg/mL, P = .02). After 15 days of SJW intake, the area under the plasma concentration-time curve from hour 0 to infinity was reduced by 59% compared with control (9.63 ± 6.03 h · μg/mL versus 23.5 ± 15.6 h · μg/mL, P = .0004), with a corresponding increase in oral voriconazole clearance (CL/F) from 390 ± 192 to 952 ± 524 mL/min (P = .0004). The baseline CL/F of voriconazole and the absolute increase in CL/F were smaller in carriers of 1 or 2 deficient CYP2C19*2 alleles compared with wild-type individuals (P < .03). Conclusions Coadministration of SJW leads to a short-term but clinically irrelevant increase followed by a prolonged extensive reduction in voriconazole exposure. SJW might put CYP2C19 wild-type individuals at highest risk for potential voriconazole treatment failure. Clinical Pharmacology & Therapeutics (2005) 78, 25-33; doi: 10.1016/j.clpt.2005.01.024
Gesehen am 18.05.2021